The role of erythrocyte membrane phospholipids in the formation of the resistance of fish organism to the action of cadmium ions - Senyk, J. I.; Khomenchuk, V. A.; Kurant, V. Z.; Grubinko, V. V. (Reports of the National Academy of Sciences of Ukraine, 2014)
The changes in the phospholipid content of erythrocyte membranes of carp (Cyprinus carpio L.) and pike (Esox lucsus L.) by the action of 0.005 and 0.02 mg/dm3 cadmium ions are studied. The redistribution of choline-containing phospholipids, reduction of phosphatidylinositol, and phosphatidylethanolamine accumulation are revealed. Such changes in the phospholipids fraction content are due to a direct action of metal on their metabolism and a mobilization of the pool with the purpose of the respective phospholipid lipid bilayer structural rearrangements in the direction counter the influence of fluorine, especially by counteracting the penetration of these ions.